2021
DOI: 10.29219/fnr.v65.5453
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol stimulates microRNA expression during differentiation of bovine primary myoblasts

Abstract: Background: Resveratrol (RSV), a phenolic compound, is present in many human dietary sources, such as peanuts, peanut butter, grapes skin, and grape wine. RSV has been widely known for its benefits on human health. Beef from cattle skeletal muscle is one of the main sources of protein for human consumption. Previous studies have also found that pork and chicken qualities are influenced by the feed supplementation with RSV. In addition, our previous study demonstrated the RSV effects on bovine myoblast differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Using 18,329 mRNA and 650 miRNA data for the sample clustering, we found that the samples with RSV treatment were clustered together in mRNA analysis (Figure 3A), while Differentially expressed (DE) mRNA and miRNA results were achieved from our previous study (31,32).…”
Section: Module Identification Of the Gene Co-expression Network For ...mentioning
confidence: 92%
See 4 more Smart Citations
“…Using 18,329 mRNA and 650 miRNA data for the sample clustering, we found that the samples with RSV treatment were clustered together in mRNA analysis (Figure 3A), while Differentially expressed (DE) mRNA and miRNA results were achieved from our previous study (31,32).…”
Section: Module Identification Of the Gene Co-expression Network For ...mentioning
confidence: 92%
“…The cultured primary myoblasts from the fetal beef longissimus dorsi muscle, the transcriptome sequencing datasets after quality control and alignment, and the differential expression analysis results were achieved from our previous studies (31,32).…”
Section: Primary Bovine Myoblast Transcriptome Sequencing and Differe...mentioning
confidence: 99%
See 3 more Smart Citations